Towards a human rights culture in South Africa. The role of moral formation - Koopman, NN (Nederduitse Gereformeerde Teologiese Tydskrif, 2007)
In this article it is argued that the building of a human rights culture entails the fulfilment of rights through measures like the cherishing and strengthening of a vision of human dignity and human rights for all, the transformation of public policies and laws so that they can adhere to a human rights vision, the development of theories that enhance the implementation of rights, the influencing of public opinion, the mobilizing of political will, the development of an ethics of responsibility, and the strengthening of the process of moral formation. The focus of this article is on last-mentioned initiative that aims at building citizens of public virtue and character who embody the human rights vision. For human rights to be fulfilled we need right humans. With reference to the work of various authors in theology and other disciplines, especially Dutch theologian Hans van der Ven, the process of moral formation is discussed. Reference is made to issues like definitions of moral formation, pragmatic and theological rationales for moral formation, as well as to spaces and modes of moral formation.